2020
DOI: 10.1111/dom.14134
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, obesity and COVID‐19: A complex interplay

Abstract: With the accumulation of observational data showing an association of metabolic co‐morbidities with adverse outcomes from COVID‐19, there is a need to disentangle the contributions of pre‐existing macro‐ and microvascular disease, obesity and glycaemia. This article outlines the complex mechanistic and clinical interplay between diabetes and COVID‐19, the clinical and research questions which arise from this relationship, and the types of studies needed to answer those questions. The authors are clinicians and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 58 publications
2
61
0
6
Order By: Relevance
“…These conditions all represent risk factors that could trigger poorer prognoses in cases of COVID-19 [11] . On the other hand, metformin is more commonly used in obese patients with T2DM [10] , and obesity has been demonstrated to be associated with a greater risk of severe COVID-19 infection and a higher mortality rate [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions all represent risk factors that could trigger poorer prognoses in cases of COVID-19 [11] . On the other hand, metformin is more commonly used in obese patients with T2DM [10] , and obesity has been demonstrated to be associated with a greater risk of severe COVID-19 infection and a higher mortality rate [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been the most popular glucose-lowering agent during the past two decades worldwide, and around two-thirds to three-quarters of patients with T2DM are treated with metformin alone or in combination. The United Kingdom Prospective Diabetes Study (UKPDS) [10] showed that metformin reduces mortality in obese patients with newly diagnosed T2DM, and obesity has been reported to be a major risk factor for developing severe COVID-19 [11] , [12] . Thus, it is of major importance to know the effect of metformin on the clinical outcomes of patients with T2DM during the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…The available data do show no increased or even lower maternal mortality rate after infection [25], but it does not mean that pregnancy is a protective factor for severe infection. It was reported that severe infection mostly occurred in the elderly (> 60 years old), patients with basic diseases, such as diabetes, obesity, hypertension, coronary heart disease, cerebrovascular diseases, and other chronic diseases [26][27][28][29][30], as well as those who did not receive timely treatment or delay treatment [31]. Pregnant women are usually younger without primary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed various percentages of COVID-19 patients with type 2 diabetes, as 20% [ 15 ], 52% [ 16 ], 24.9% [ 17 ], 14.5% [ 18 ], and 21.8% [ 19 ]. However, a number of studies have shown that the severity and complications of COVID-19 disease and the need for ICU stay were higher in diabetic patients than in non-diabetic individuals [ 9 , 14 , 15 , 17 , 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher rate of mortality in diabetic patients can be due to their weakened immune system [ 26 ], poor lung function, and reduced lung capacity along with their common respiratory problems [ 18 ]. Furthermore, COVID-19 can affect diabetes pathogenicity as well as blood sugar control [ 20 ], all of which together can lead to increased mortality rate among these people. However, further research is needed to find out if COVID-19-related mortality was actually caused by diabetes or other factors, as most of these people are elderly and may have at the same time some other chronic diseases, including hypertension and cardiovascular disease, which makes it a little difficult for us to identify the main cause of death due to COVID-19.…”
Section: Discussionmentioning
confidence: 99%